Oketani massage with jasmine oil improves breast milk production on postpartum days 1-3 - Ni Made Ratih Comala Dewi; Made Ririn Sri Wulandari; Yupin Aungsuroch (Wolters Kluwer Medknow Publications, 2024)
Objective: This study aimed to determine the effect of Oketani massage with jasmine oil on improving breast milk production on days 1-3. Materials and Methods: This preexperimental one-group pretest-posttest design was conducted with 44 eligible respondents, selected using an incidental sampling technique. Oketani massage with jasmine oil was conducted once a day for 3 consecutive days. A total of 44 respondents were selected with incidental sampling. Sufficient breast milk production was observed through the frequency of baby urination in 24 h, the frequency of baby defecation in 24 h, the baby's weight, and the length of time the baby slept or remained calm after breastfeeding. Results: Results showed that Oketani massage using jasmine oil impacted on increasing breast milk production in postpartum on days 1-3 (Z = 6.633, P = 0.000). The baby's weight in 3 days was increased after intervention compared with intervention before (2858.25 ± 180.62 g vs. 2881.66 ± 180.96 g, t = 55.33, P = 0.000), the baby's urination frequency was increased after intervention (4.55 ± 0.50 vs. 7.20 ± 0.70, t = 17.87, P = 0.000), the breastfeeding frequency has decreased (10.27 ± 1.42 vs. 8.82 ± 0.82, t = 6.94, P = 0.000), and the time of baby's sleeping or calming state has increased (5.14 ± 6.46 h vs. 8.48 ± 10.24 h, t = 2.11, P = 0.041). Conclusion: Oketani massage combined with jasmine oil has been shown to be effective on improving breast milk production on days 1-3.